2019
DOI: 10.9734/jamb/2019/v18i230168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera lam. Leaf Powder on Bifidobacteria and Escherichia coli in the Gut of Albino Rats

Abstract: Aim: This study was carried out to determine the effects of dried Moringa oleifera leaves on Bifidobacteria and Escherichia coli in the gut of albino rats. Location: The rats were habituated under laboratory conditions at the animal house of the Department of Zoology, Faculty of Science, University of Ibadan, for two weeks in other to adapt to the environmental conditions during the experiment. Duration of Study: The rats were exposed to the M. oleifera feed for four weeks. Design of Study: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, the intestinal microbiota and its stability depend on intrinsic factors of the host, such as age, gender and genotype, as well as extrinsic factors such as habitat and diet (Ringø et al, 2016; Xu & Knight, 2015). Therefore, diet additive including probiotic or herbal supplements, affects the intestinal microbiota and may lead to a balance in the gut microbial population by improving the growth of beneficial bacteria (Abidin et al, 2022; Amoah et al, 2020; Gbadebo et al, 2019; Habiba et al, 2021; Munaeni et al, 2020). In this study, the total number of heterotrophic bacteria in the intestine decreased significantly with an increase in the concentration of paprika extract.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intestinal microbiota and its stability depend on intrinsic factors of the host, such as age, gender and genotype, as well as extrinsic factors such as habitat and diet (Ringø et al, 2016; Xu & Knight, 2015). Therefore, diet additive including probiotic or herbal supplements, affects the intestinal microbiota and may lead to a balance in the gut microbial population by improving the growth of beneficial bacteria (Abidin et al, 2022; Amoah et al, 2020; Gbadebo et al, 2019; Habiba et al, 2021; Munaeni et al, 2020). In this study, the total number of heterotrophic bacteria in the intestine decreased significantly with an increase in the concentration of paprika extract.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic microbiologists were more interested in studying the gut microbiota because it plays a significant role in the growth of its hosts through a variety of mechanisms, such as producing digestive enzymes for food digestion (Amin, 2018), excreting vitamins , and producing short-chain fatty acids (SCFAs) (Hoseinifar et al, 2017). Dietary management, such as probiotic and prebiotics supplementation, affects the gut microbiota composition (Gbadebo et al, 2019;Amoah et al, 2020;Munaeni et al, 2020). The growth performance of shrimp fed with diets containing a combination of a probiotic and a prebiotic is higher than that of shrimp fed with diets containing a probiotic or prebiotic alone (Abidin et al, 2022) Moreover, many researchers also found an increase in growth performance by using multiple probiotics (Lee et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, flavonoids are found to have a large anti-oxidant function and increase urination and electrolyte excretion, which functions like potassium that absorbs electrolyte ions. 27 In addition, the phenolic chemicals in moringa are multi-functional compounds that are useful for pregnant women and children in preventing cell damage, diseases and aging. 28 Previous research also shows that giving EG to pregnant women increases the quantity of their breast milk.…”
Section: Articlementioning
confidence: 99%